1995
DOI: 10.1038/sc.1995.42
|View full text |Cite
|
Sign up to set email alerts
|

A nationwide epidemiological survey of spinal cord injuries in Japan from January 1990 to December 1992

Abstract: was carried out by a statistical method of the nationwide epidemiological study. The number of the registered patients during these 3 years was 9752 and the mean response rate of every of the 47 prefectures was 51.4%. The registered patients with neurological deficits (Frankel A-D) were 7471 and the annual spinal cord injury incidence was 40.2 per million. The ratio of cervical cord injuries to more caudal SCI was 3:1. The age distribution and the causes of spinal cord injuries are presented in detaiL From the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
74
1
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(83 citation statements)
references
References 7 publications
6
74
1
1
Order By: Relevance
“…Our male to female ratio of 7.5 : 1.0 is higher in Japan and in Jordan, 3,6 and this is not surprising in a country such as Bangladesh where the majority of women remain in the home as housewives, and are not subject to the more violent forms of accidents to which men are exposed. This supports the tenets of Kuhn 7 who concluded that`the sex ratio re¯ects the socioeconomic and cultural status of a society'.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Our male to female ratio of 7.5 : 1.0 is higher in Japan and in Jordan, 3,6 and this is not surprising in a country such as Bangladesh where the majority of women remain in the home as housewives, and are not subject to the more violent forms of accidents to which men are exposed. This supports the tenets of Kuhn 7 who concluded that`the sex ratio re¯ects the socioeconomic and cultural status of a society'.…”
Section: Discussionmentioning
confidence: 72%
“…2,6 However, in a more developed country such as Japan the average age is between 40 ± 70, with a peak at 59 years. 3 It seems that our younger patients had fallen from a signi®cant height, while thè elderly' Japanese patients had fallen while on the ground. 3 Falling from a height was the most commoǹ traumatic' cause of spinal cord injury in our series (76 patients, 43%, and RTA 18%), and this is similar to that reported from India (fall 55%, and RTA 13%), 1 Nigeria (fall 48%, and RTA 36%) 8 and Romania (fall 59%, and RTA 13%).…”
Section: Discussionmentioning
confidence: 88%
“…32,69,70 In contrast, Map 2 also demonstrates a high proportion of paraplegia secondary to high falls in Asia, South (Pakistan, Bangladesh and Nepal) as well as a component of low falls (Bangladesh). [71][72][73] Violence-related TSCI occurs in regions of conflict or high availability of weapons (gunshot wounds and stabbings).…”
Section: Discussionmentioning
confidence: 99%
“…21 Lin et al reported an even higher proportion of complete lesions 22 while most of the other series 3,6,7,12,15 show a majority of incomplete injuries. It is worth noting that the most recent studies 21,22 are the ones that found the largest number of complete injuries.…”
Section: Cervical Cord Injurymentioning
confidence: 95%
“…Some surveys would appear to deal with populations recruited using very di erent options. 3 Therefore, it may sometimes be di cult to establish ®rm grounds for making comparisons.…”
Section: Introductionmentioning
confidence: 99%